Erythrocyte ENT1-AMPD3 Axis is an Essential Purinergic Hypoxia Sensor and Energy Regulator Combating CKD in a Mouse Model - Chen, Changhan; Xie, TingTing; Zhang, Yujin; Wang, Yiyan; Yu, Fang; Lin, Lizhen; Zhang, Weiru; Brown, Benjamin C; Zhang, Xin; Kellems, Rodney E; D'Alessandro, Angelo; Xia, Yang (Journal of the American Society of Nephrology, 2023)
Hypoxia drives kidney damage and progression of CKD. Although erythrocytes respond rapidly to hypoxia, their role and the specific molecules sensing and responding to hypoxia in CKD remain unclear. In this study, we demonstrated in a mouse model that erythrocyte ENT1-AMPD3 is a master energy regulator of the intracellular purinergic hypoxic compensatory response that promotes rapid energy supply from extracellular adenosine, eAMPK-dependent metabolic reprogramming, and O 2 delivery, which combat renal hypoxia and progression of CKD. ENT1-AMPD3-AMPK-BPGM comprise a group of circulating erythroid-specific biomarkers, providing early diagnostic and novel therapeutic targets for CKD. Hypoxia drives kidney damage and progression of CKD. Although erythrocytes respond rapidly to hypoxia, their role and the specific molecules sensing and responding to hypoxia in CKD remain unclear. Mice with an erythrocyte-specific deficiency in equilibrative nucleoside transporter 1 ( eEnt1-/- ) and a global deficiency in AMP deaminase 3 ( Ampd3-/- ) were generated to define their function in two independent CKD models, including angiotensin II (Ang II) infusion and unilateral ureteral obstruction (UUO). Unbiased metabolomics, isotopic adenosine flux, and various biochemical and cell culture analyses coupled with genetic studies were performed. Translational studies in patients with CKD and cultured human erythrocytes examined the role of ENT1 and AMPD3 in erythrocyte function and metabolism. eEnt1-/- mice display severe renal hypoxia, kidney damage, and fibrosis in both CKD models. The loss of eENT1-mediated adenosine uptake reduces intracellular AMP and thus abolishes the activation of AMPK α and bisphosphoglycerate mutase (BPGM). This results in reduced 2,3-bisphosphoglycerate and glutathione, leading to overwhelming oxidative stress in eEnt1-/- mice. Excess reactive oxygen species (ROS) activates AMPD3, resulting in metabolic reprogramming and reduced O 2 delivery, leading to severe renal hypoxia in eEnt1-/- mice. By contrast, genetic ablation of AMPD3 preserves the erythrocyte adenine nucleotide pool, inducing AMPK-BPGM activation, O 2 delivery, and antioxidative stress capacity, which protect against Ang II-induced renal hypoxia, damage, and CKD progression. Translational studies recapitulated the findings in mice. eENT1-AMPD3, two highly enriched erythrocyte purinergic components that sense hypoxia, promote eAMPK-BPGM-dependent metabolic reprogramming, O 2 delivery, energy supply, and antioxidative stress capacity, which mitigates renal hypoxia and CKD progression.